(3ebGdI aj Cf GdYQV djS gh LfSkG ddJSY GdebhdGJ GdYQVjIs - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3bGd Gfg deG cGf QSe GdLfS HeG gh LfS hcGf bO jbGd ai cd hGMO ef GdGLfGS GdJSYI GdYQVjI s
(3BNQgG (B:s
(3ef GLfGS GdGYQGV GdYGQVjI ddMb Hg gh eYfi GdYQV hYcS gPG GdeYfi GdYQVi djS gh hdG hGMOkG ef GLfGS GdGYQGV GdYGQVI JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B13 - (3U(B19s
(3GfXQg eY GdeNWhW Qbe (B302 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(3/4901) s
Keywords: (3GdadSaI hGdefWbs